A new species of thrip, genus Frankliniella(group cephalica; Thysanoptera: Thripidae) from Costa Rica - Retana-Salazar, Axel P (2005)
A new species of the Frankliniella cephalica group, from Central Costa Rica, is described under the name “Frankliniella morerai n.sp.”. It is closely related to Frankliniella sandovalensis. Both species have translucent bodies, but the new species can be distinguished by these characteristics: setae io III in position 1/2, a complete comb on abdominal segment VIII, antennal segments without coloration and setae po IV longer. It was found in low density in crops of chilli, tomato, lettuce, sweet potato and coriander. A comparative table with other species of this group is included to facilitate diagnosis.